„For the hearse straight to the cemetery…” – organization and costs of a landowner’s funeral on the example of the last journey of the Tekla from Walewski family countess Walewska - Czekalska, Adrianna (Requiem, 2025)
The only certain „thing” in human life is death. From an anthropological and historical perspective, a funeral is a source about culture at a specific time and in a specific group. A funeral may be therefore a source if information about the social status of deceased and the organizers. A very interesting example of burials in urban space are those performed for people belonging to wealthy landed gentry. The aim of the article is to present the funeral of Tekla from the Walewski family, countess Walewska, which was the wife of the president of the Heraldry of the Congress Poland, Aleksander count Walewski. To confirm the thesis about the special wealth of landowner burials, I used a comparison with the celebrations for Aleksander Leon Lesznowski, the owner of “Gazeta Warszawska”.